Framing blame: toward a better understanding of the effects of populist communication on populist party preferences. Issue 3 (3rd July 2018) - Hameleers, Michael; Bos, Linda; de Vreese, Claes
ABSTRACT: Although previous research has argued that the media play a crucial role in populism's success, we know too little about how populist messages affect preferences for populist parties. To advance this knowledge, we conducted an experiment in which the core of populist rhetoric – constructing the people as innocent in-group opposed to the establishment as culprit out-group – was manipulated in news articles. The findings indicate that when political elites are blamed for a salient national problem, people are more likely to vote for a populist party and less likely to vote for the largest party in government. Populist vote intentions are indirectly affected via blame perceptions. These findings offer important insights into the media's role in the electoral success of populism.